1998
DOI: 10.1507/endocrj.45.377
|View full text |Cite
|
Sign up to set email alerts
|

Pinealectomy or Melatonin Implantation Does Not Affect Prolactin Surge or Luteal Function in Pseudopregnant Rats.

Abstract: Abstract. The effects of melatonin on twice daily surges in PRL and luteal function were studied in pseudopregnant (PSP) rats. Cyclic rats received pinealectomy or sham operation under pentobarbital anesthesia on diestrus 1. Pinealectomized rats immediately received a melatonin capsule (the PINX+Mel group) or a blank capsule (the PINX group), and sham group of rats received a blank capsule (the control group). After operation, all rats were maintained under the same photoperiod conditions (14L: 10D), and estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Intrafollicular concentrations of melatonin were measured by radioimmunoassay as reported previously [32]. Briefly, serum melatonin (500 mL) was extracted with 2 mL of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…Intrafollicular concentrations of melatonin were measured by radioimmunoassay as reported previously [32]. Briefly, serum melatonin (500 mL) was extracted with 2 mL of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…Serum melatonin concentrations were measured by radioimmunoassay, as reported previously [19]. Briefly, 500 μ L of serum was extracted with 2 mL of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…Melatonin plays a key role in a variety of important physiological functions, including circadian rhythms [7], reproductive [8], neuroendocrine [9], cardiovascular [10], neuroimmunological [11], oncostatic actions [12]. We already reported that melatonin plays a role in lipid metabolism [13], pregnancy and parturition time [14-16], and corpus luteum (CL) function [17]. Some effects of melatonin are mediated through specific membrane receptors, but many of them seem to rely on its potential as a direct free radical scavenger, a process that requires no receptor.…”
Section: Intoductionmentioning
confidence: 99%